Pengaruh Suplementasi Tepung Jintan Hitam dan Tepung Daun Mengkudu terhadap Organ Reproduksi Puyuh Betina - Masir, Ummul; Alwi, Windawati; Nur, Khaeriyah; Zulkarnain, Ahmad; Permatasari, Gita (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Quail (Coturnix coturnix japonica) is an egg-producing poultry species whose optimal egg production relies on reproductive health, which can be supported by adding herbal supplements to the feed. This study investigated the potential of black cumin meal (BCM) and noni leaf meal (NLM) on the reproductive quality of female quail. Ninety-six heads of quails aged 66 days were maintained for 28 days with the following treatment: T0= Basal Feed (BF); T1= BF + 1% BCM + 3% NLM; T2= BF + 2% BCM + 3% NLM; T2= BF + 2% BCM + 2% NLM; T3= BF + 3% BCM + 1% NLM. Two head quails in each unit were necropsied to observe the parameters of the study, such as: weight and length of the oviduct, oviduct presentation, reproductive organ presentation, ovary weight, number and weight of yellow follicles, and weight of white follicles. The data were analyzed using a completely randomized design (CRD) with four treatments and three replications. The results showed that BCM and NLM supplementation only affected the weight of the oviduct and ovary (P<0.05); otherwise, there was no effect (P>0.05). No additional protein source is responsible for this finding; instead, the antioxidant content of the supplement serves to maintain livestock health. A combination of BCM and NLM can be recommended as a feed supplement at a rate of up to 1-3%.